Europäische Schienenverkehrsstudie 2006 - Aufbruch in unsichere Zeiten. - Elders, Volker; Pulver, Thorsten; Reinecke, Rolf (Deutscher Verkehrs-Verl., 2006)
Der europäische Schienenverkehrsmarkt verändert sich dramatisch. Die Befragung von 27 Topbahnmanagern aus 13 kontinentaleuropäischen Ländern im Jahr 2005 verdeutlicht die veränderten Rahmenbedingungen und künftigen Entwicklungen auf dem europäischen Schienenverkehrsmarkt. Thematisiert werden Konsequenzen für Unternehmen und unternehmerische Reaktionen auf die neuen Herausforderungen. Die Befragung wurde von der internationalen Unternehmer-Beratung Droege & Comp. GmbH gemeinsam mit der Universität Gießen durchgeführt. difu

The study presented - based on a pan-European survey of rail transportation operators conducted by the international management consultancy Droege & Comp., in cooperation with Prof. Dr. Gerd Aberle of Giessen University - delivered important insights into current market and competitive conditions, expected developments and entrepreneurial reactions to present and anticipated changes. The results of this investigation can be summarized as follows: The pan-European liberalization of the rail traffic market and the eastern expansion of the EU offer an opportunity to significantly increase the railway's market share of European freight and passenger transport operations compared to other modes of transport; increasing market dynamics and stronger inter-/intramodal competition will result, on the one hand, in an increased efficiency and competitive ability of he railway system; but a lasting competitive lead will only be reached by combining strategic and operative activities; realization of cost reduction potentials, raising of market-specific service quality and development of customer-oriented mobility concepts will be the most important levers on the track of operational excellence. difu difu
Keywords: Öffentlicher Verkehr; Schienenverkehr; Verkehrsunternehmen; Güterverkehr; Befragung; Marktforschung; Eisenbahn; Wettbewerb; Verkehrsmarkt; Nachhaltigkeit